The Alfalfa Yield Gap: A Review of the Evidence. Issue 1 (1st December 2013) - Russelle, Michael P.
Abstract : Knowledge of feasibly attainable crop yields is needed for many purposes, from field‐scale management to national policy decisions. For alfalfa ( Medicago sativa L.), the most widely used estimates of yield in the US are whole‐farm reports from the National Agriculture Statistics Service, which are based on the farmer's estimates of total production. These reports combine establishment‐year and production‐year harvests, which may inadvertently reduce yield expectations for production‐year stands. However, some reported yields were unrealistically high, indicating a previously unreported problem with forage yield reports. This article presents new summaries of information from the small‐plot to the whole‐farm scale, which support the conclusion that dry hay yields (13% moisture) greater than 8 tons/acre are feasible under irrigation in the West and yields greater than 6 tons/acre are feasible under nonirrigated conditions in many states in the East. There is a yield gap of 2‐ to threefold between average and top‐tier producers in most states. Bridging that gap should greatly improve farm profitability and availability of the product.